A study of the leisure motivation behaviour of Singaporeans with the Night Safari as a case example. - Singh, Dalbir Jhol. (2008)
The purpose of this study is to research into the leisure motivation behavior of Singaporeans. A better understanding of Singaporeans’ leisure motivation habits will certainly help the local attractions to position themselves strategically. A great deal of literature review was then reviewed to identify various methods of categorizing the leisure behaviors. Based on Ragheb and Beard’s study, a survey was formulated to help identify the various leisure motivation types.